STABILITY INDICATING METHOD DEVELOPMENT AND VALIDATION FOR THE DETERMINATION OF METFORMIN AND DAPAGLIFLOZIN BY RP-HPLC - TejNarayan Tharu, Obed Singh, Dr. Shivanand Patil (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
A simple, Accurate, precise method was developed for the simultaneous estimation of the Metformin and Dapagliflozin in Tablet dosage form. The chromatogram was run through Kromasil 250 x 4.6 mm, 5m. Mobile phase containing Buffer and Acetonitrile in the ratio of 60:40A was pumped through column at a flow rate of 1ml/min. Buffer used in this method was 0.1% OPA buffer and the Temperature was maintained at 30°C. Optimized wavelength for Metformin and Dapagliflozin was 266nm. The retention time of Metformin and Dapagliflozin were found to be 2.330min and 3.098 min. %RSD of the Metformin and Dapagliflozin were and found to be 0.7 and 0.8 respectively. %assay was obtained as 99.57% and 99.76% for Metformin and Dapagliflozin respectively. LOD, LOQ values are obtained from regression equations of Metformin and Dapagliflozin were 0.90ppm, 2.73ppm and 0.02ppm, 0.07ppm respectively. Regression equation of Metformin & Dapagliflozin is y = 2433.x + 15236 and y = 13061x + 672.2. Retention times are decreased and that run time was decreased so the method developed was simple and economical that can be adopted in regular Quality control test in Industries.